HUBUNGAN MOTIVASI ORANG TUA DENGAN KEBERADAAN TELUR CACING PADA TINJA SISWA DI SDN 1 SUKAWATI KABUPATEN GIANYAR - Anak Agung Ary Dwiutami; Ni Ketut Rusminingsih; I Ketut Aryana (Jurnal Kesehatan Lingkungan (JKL), 2019)
Bali province is one of provinces in Indonesia whose community especially children aged 5-12 years who still have intestinal worms infection with varying prevalence. This research is done in order to know the relationship of parents' motivation with the existence of worm eggs in the stools of students at SDN 1 Sukawati. This research is an analytical survey with cross sectional study design. The number of samples from this study are 67 respondents and 67 samples of stool students. Statistical test analysis in this study using Chi Square analysis method (X2). Characteristics of respondents obtained the dominant of age parents and students are between 38-43 years (52%) and students between 9-11 years (48%). The dominant of parents' education and the sex of the students are senior high school (47%) and female (52%). The relationship of parents' motivation with the existence of worm eggs in the stools of students is undefined because the existence of worm eggs in stool students is constant or all (100%) of samples stool are negative worm eggs. Various factors other than motivation can influence it. Nevertheless, parents should still motivate students to prevent intestinal worms because the disease can be infected at any time.